Social memory and political transition: Denying the colombian internal armed conflict in the coffee region - Berón Ospina, Alberto Antonio; Martínez Herrera, Luis Adolfo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The immeasurable impacts of the internal armed conflict experienced in Colombia continuously transform the different spheres of daily life. In this context, the coffee region experiences a social imaginary that denies the armed conflict in order to consolidate a development project in its territory. This article, the result of a qualitative cohort research project and the dialogue between relational sociology and historical philosophy, is intended to analyze the relationships between transitions and memories in contexts nuanced by historical violence, recognizing control devices that generate concealment of the conflict, but also practices of resistance in the coffee region.